The rebound of the body using running-specific prostheses in unilateral transfemoral amputees - Murata, H.; Hisano, G.; Amma, R.; Takemura, H.; Hobara, H. (ISBS Proceedings Archive (Michigan), 2020)
Although the elastic bounce of the body is considered a prerequisite for running, the rebound strategy in individuals with lower extremity amputation is not well known. This study aims to investigate the rebound strategy at different running speeds in unilateral transfemoral amputees (uTFAs) wearing running-specific prostheses (RSPs). On an instrumented treadmill, eight uTFAs ran at incremental speeds (30%, 40%, 50%, 60%, 70%, and 80% of the average speed of their 100-m personal records). The rebound strategy of the unaffected and affected limbs is evaluated using the ratio of the natural frequency of the spring-mass system (fsist) to the step frequency (fstep). At all speeds, fsist/fstep in the unaffected limb is considerably greater than that in the affected one. The interlimb differences in fsist/fstep tended to increase with the speed. These results suggest that the rebound strategy is not the same for the unaffected and affected limbs in uTFAs across a range of speeds, and that uTFAs wearing RSPs perform bouncing steps using the alternate asymmetric rebound strategy (fstep < fsist) through different limbs.